2011
DOI: 10.1186/1471-2458-11-s3-s14
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of malaria case management and intermittent preventive treatment for preventing malaria mortality in children: a systematic review for the Lives Saved Tool

Abstract: BackgroundThe Lives Saved Tool (LiST) model was developed to estimate the impact of the scale-up of child survival interventions on child mortality. New advances in antimalarials have improved their efficacy of treating uncomplicated and severe malaria. Artemisinin-based combination therapies (ACTs) for uncomplicated Plasmodium falciparum malaria and parenteral or rectal artemisinin or quinine for severe malaria syndromes have been shown to be very effective for the treatment of malaria in children. These inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 69 publications
0
69
0
3
Order By: Relevance
“…This is especially the case for which is close to linearly related to . If is much greater than the OpenMalaria value of (and therefore also higher than the core estimates, as in Thwing et al [4]) then the primary estimates substantially understate the variation between countries in the incidence of severe malaria cases that are not admitted.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This is especially the case for which is close to linearly related to . If is much greater than the OpenMalaria value of (and therefore also higher than the core estimates, as in Thwing et al [4]) then the primary estimates substantially understate the variation between countries in the incidence of severe malaria cases that are not admitted.…”
Section: Resultsmentioning
confidence: 85%
“…Hospital case fatality rates for well-defined severe malaria are relatively well established [2, 3]. However these do not translate directly into estimates of the impact of effective management of severe disease on malaria mortality rates, for which only estimates based on expert opinion are available [4] and, to date, there are no good estimates of how these translate into numbers of malaria deaths averted.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials of ACTs in different parts of Nigeria since its introduction have shown good efficacy and tolerability of ACTs in the treatment of uncomplicated malaria in children [7,8]. The high cure rates of ACTs have also been confirmed in different studies across sub-Saharan Africa [9].…”
Section: Introductionmentioning
confidence: 85%
“…7,8 As a result of the ability of the artemisinin component to rapidly reduce para sitemia, early treatment of uncomplicated malaria with ACTs may prevent progression to severe disease, thereby reducing the number of severe cases and the malaria mortality rate. 9 The ACTs may also reduce overall malaria transmission by decreasing human infectivity to mosquitoes 10,11 and by extending the prophylactic period after treatment. 8 A variety of ACTs exists, such as artemether-lumefantrine (AL) and dihydroartemisinin-piperaquine (DP), which vary in their efficacy profile against uncomplicated malaria, tolerability, and their ability to reduce infectivity to mosquitoes.…”
Section: Introductionmentioning
confidence: 99%